Photographing the Corporate Social Responsibility Program in the Field of Education Based On The Political Economy Of Accounting Theory - Mariam Ulayya; Mazni Abdullah; Ayudia Sokarina; Adhitya Bayu Suryantara (TIJAB (The International Journal of Applied Business), 2023)
Background: Every company that establishes and conducts business must comply with all applicable legal regulations in the country, including those for coal mining companies, ranging from labor rules to rules related to environmental sustainability. Generally, companies are founded with the aim of making a profit, but nowadays many companies are not only oriented towards this but also social and educational life. As a result of this shift in orientation, the concept of corporate responsibility named Corporate Social Responsibility (CSR) emerged. Objective: The purpose of this study is to photograph the Corporate Social Responsibility program in the field of education, namely X School, based on the theory of the Economy of Accounting. Method: This is qualitative research with the type of Dicipline Comparative Studies or case studies that aim to compare the cases studied with established theories. The data collection technique is carried out through interviews, observations, and documentation. Results: The results of this study show that the implementation of CSR programs is a company's effort to link and match school education programs with the industrial world. Meanwhile, the role of mining regulation is shown through the Law on the obligation to carry out Social and Environmental Responsibility for companies whose business activities are in the field of or related to natural resources and the X Regency regional regulation, which regulates the company's obligation to hire local workers by as much as 80%. Conclusion: The distribution of education in the implementation of the X School program has been evenly distributed and fair because it reaches communities around the mining operational area and is aimed at residents who are directly adjacent to the company, so that the benefits of the company's existence can be felt directly. Keywords: Corporate Social Responsibilty, Education, Political Economy of Accounting, X School